Dental Trauma and Mouthguard Usage among Soccer Players in Izmir, Turkey - Ilhan Uzel; Arzu Aykut-Yetkiner; Nazan Ersin; Fahinur Ertugrul; Ozant Oncag; Rengin Attin (MDPI AG, 2014)
The aims of this study were to verify the occurrence of dental injuries in 343 amateur Turkish soccer players in İzmir and the level of knowledge of the teams' soccer players about mouthguards. The soccer players were interviewed to determine the occurrence of dental trauma during soccer and mouthguard usage level. The data were analyzed with descriptive analysis to determine absolute and relative frequencies of answers for each one of the questions. Only 35 (10.2%) soccer players reported the occurrence of some type of dental injury during soccer practice. Regarding emergency conducts, approximately 84 players (24.48%) answered that replantation could be obtained after teeth avulsion, 23 players (27.38%) answered that successful replantation could be obtained within 2 hours immediately after injury, and 60.71% were not able to answer this question. Regarding mouthguard use, 61.8% of soccer players did not know about mouthguards. It was possible to conclude that dental injuries are common during amateur soccer practice and that there is a lack of information in the soccer players related to the emergency conducts and prevention of dental trauma.